Blood constituents during the estrous cycle and early pregnancy in dairy cows - Johnson, S K; Johnson, A R; Keefer, C L; Silcox, R W (Theriogenology, 1990)
The objective of this study was to determine if maternal platelet count, white blood cell count or other blood constituents undergo sustained alterations in concentration following fertilization. Blood samples from 17 Holstein females were collected over an 18-d period starting at estrus. Blood was analyzed for levels of platelets, white blood cells, red blood cells, hemoglobin and hematocrit. Results were analyzed for differences between nonpregnant and pregnant groups. Analysis of variance revealed a day-by-group interaction in the platelet count (P<0.01). White blood cell count showed both a day-by-group interaction and a difference between days (P<0.01). Red blood cell count, hematocrit and hemoglobin levels resulted in no significant difference between the two groups (P>0.05). While statistically significant differences were observed in platelet and white blood cell count, neither of these were sustained over a period longer than 2 d.